2007
DOI: 10.2217/14796678.3.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Nematode Anticoagulant Protein c2 in non-ST Segment Elevation Acute Coronary Syndrome and Beyond

Abstract: Patients with acute coronary syndromes (ACS) have high recurrent ischemic event rates despite management with current guideline-based therapies. Recombinant nematode anticoagulant protein (rNAP)c2 provides factor Xa-dependent inhibition of the tissue factor/factor VIIa complex acting proximally on the clotting cascade. It may be administered either intravenously or subcutaneously and has an elimination half-life of approximately 50-60 h. rNAPc2 reduces thrombin formation in patients undergoing elective percuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In a double blind placebo-controlled trial, rNAPc2 was found to be safe and well-tolerated at doses ranging from 0.3 to 5 μg/kg body weight in preventing thrombin generation during coronary angioplasty in combination with aspirin, clopidogrel, and heparin (Moons et al, 2003). A more recent phase II clinical study demonstrated that in patients with non ST-elevation acute coronary syndrome managed with standard antithrombotics and an early invasive approach, additional proximal inhibition of the coagulation cascade with rNAPc2 was well tolerated and not associated with an increase in major or minor bleedings as compared with a placebo treatment (Fluture et al, 2007;Giugliano et al, 2007). A novel finding in the ANTHEM-TIMI-32 trial was that the doses of rNAPc2 suppressing thrombin generation through 48 h were associated with a ≥50% reduction in ischemia on continuous ECG.…”
Section: Nematode Anticoagulant Protein (Napc2)mentioning
confidence: 99%
“…In a double blind placebo-controlled trial, rNAPc2 was found to be safe and well-tolerated at doses ranging from 0.3 to 5 μg/kg body weight in preventing thrombin generation during coronary angioplasty in combination with aspirin, clopidogrel, and heparin (Moons et al, 2003). A more recent phase II clinical study demonstrated that in patients with non ST-elevation acute coronary syndrome managed with standard antithrombotics and an early invasive approach, additional proximal inhibition of the coagulation cascade with rNAPc2 was well tolerated and not associated with an increase in major or minor bleedings as compared with a placebo treatment (Fluture et al, 2007;Giugliano et al, 2007). A novel finding in the ANTHEM-TIMI-32 trial was that the doses of rNAPc2 suppressing thrombin generation through 48 h were associated with a ≥50% reduction in ischemia on continuous ECG.…”
Section: Nematode Anticoagulant Protein (Napc2)mentioning
confidence: 99%